Determinación de la flora microbiológica comerciales de la canal cunícola empacados al vacío y en empaque tradicional (Bandeja de Icopor) obtenidos de una granja cunícola (2017)
Meat is an important protein source for people; they have produced it by farming largely around the world, nonetheless, in the last years the exploitation of smaller species such as the rabbit has taken great importance, mainly in Europe, since it is white, lean and juicy meat that provides a high protein content and low cholesterol, fat and energy. However, as a meat product, the consumption demand increases and so does the need to apply good manufacturing practices that ensure the traceability and safety of it. Unfortunately, the development of rabbit breeding in Colombia has been slow due to economic, cultural, and technical factors that are seen in the traditional packaging methods that are used to protect both fresh and frozen meat (plastic bags or Styrofoam trays), which expose them to constant microbiological risk; This work aimed to recognize the microbiological nature of this meat and the viability of vacuum packaging against the traditional one through the analysis of microorganisms such as Mesophiles, Psychophils, fungi and yeasts, Staphylococcus aureus, total and fecal Califormes, Clostridium sulfite reducers, Salmonella and Listeria monocytogenes, getting to the conclusion that, according to the growth dynamics observed in both packages, the vacuum did not present a considerable advantage compared to the tray, since four of the evaluated microorganisms were found above the minimum infective dose and the microbiological limits established for other meats